Candide, or Optimism - Voltaire (New York Penguin Books, 2005)
In this splendid new translation of Voltaire?s satiric masterpiece, all the celebrated wit, irony, and trenchant social commentary of one of the great works of the Enlightenment is restored and refreshed.
Includes bibliographical references (p. [121]-155).
Keywords: Voltaire, 1694-1778 --Translations into English